Chemical Conversion of CO2: Evaluation of Different Ionic Liquids as Catalysts in Dimethyl Carbonate Synthesis. (July 2017) - Vieira, Michele O.; Aquino, Aline S.; Schütz, Marta K.; Vecchia, Felipe D.; Ligabue, Rosane; Seferin, Marcus; Einloft, Sandra
Abstract: Dimethyl carbonate (DMC) synthesis from methanol and CO2 was investigated using ionic liquids (ILs) as catalysts. ILs based on 1-alkyl-3-methyl imidazolium and N-alkylpyridine cations and [Cl − ], [BF4 − ], [PF6 − ], [Tf2 N − ] anions were used in this study. Selectivity in DMC increased in the anion order: [Tf2 N − ] < [PF6 − ] < [Cl − ] < [BF4 − ], following the same behavior for both cations. Methanol conversion was similar for all tested ILs. The best result for DMC selectivity (83%) was obtained when [emim][BF4 ] was used as catalyst. After 5 recycling tests, a loss of 8.5% in the catalyst activity was observed for [bmim][BF4 ].